A ‘Manual’ of table manners in Ancient Thrace (according to Xen. Anab. 7.3) (Research Announcements "Heritage BG", 2023)
Dining etiquette is not an invention of modern society. In Antiquity, the organization of the tableforspecial occasions also followed certain rules. The reception of the guests, the sequence ofserving the dishes, and the elements of tableware and furnishings correspond to the cultural traditions of individual civilizations. The article aims to present the Thracian royal feasts as events following a certain sequence and ceremonial, rather than celebrations of chaos and intemperance, referring mainly to Xenophon’s account of the dinner organized by the Odrysian paradynast Seuthes II at the beginning of the 4th century BC. References:Primary Sources:Athenaeus, The Deipnosophist. In: http://www.perseus.tufts.edu/hopper/text?doc=Perseus%3Atext%3A2008.01.0405%3Abook%3D1%3Achapter%3D1Xenophon, Anabasis. In: http://www.perseus.tufts.edu/hopper/text?doc=Perseus:text:1999.01.0201Diodorus Siculus. Fragments. In: http://remacle.org/bloodwolf/historiens/diodore/livre21a.htmSecondary Sources:Bozhkova, A. (2016). Banketniyat serviz na drevnite traki po danni ot keramichnite nahodki. –Arheologiya, No. 57/1–2, 19 – 31.Dimitrov, D. P. (1958). Za ukrepenite vili i rezidentsii u trakite v predrimskata epoha. – In: Izsledvaniya v chest na akademik D. Dechev. Sofia, 683 – 699.Dimitrov, D. P. (1960). Gradoustroystvo i arhitektura na trakiyskiya grad Sevtopolis. – In: Arheologiya, No. 2/1, 3 – 15.Dimitrov, D. P. (1984). Trakiyskiyat grad Sevtopolis. – In: Sevtopolis I. (eds. Dimitar Petrov Dimitrov, Maria Chichikova, Ana Balkanska, Luba Ognenova-Marinova). Sofia, 11 – 17.Georgieva, R. (1999). Hrana i hranene (kraya na II – I hil. pr.n.e.) – In: Etnologiya na trakite. (eds. Rumiana Georgieva, Tosho Spiridonov, Maria Reho). Sofia, 71 – 111.Georgieva, R. (2008). Trapezata na martvite v Drevna Trakiya. – In: Ethnologia Academica 4: Balgarskite spetsifiki mezhdu traditsiyata i modernostta. (ed. Mira Markova). Sofia, 11 – 21.Izdimirski, M. (2017). Tekstil, tsvyat i simvol v trakiyski grobni nahodki ot I hil. pr. hr. . – In: KRATISTOS Sbornik v chest na profesor Petar Delev. (eds. Hristo Popov, Julia Tzvetkova). Sofia, 423 – 440.Kitov, G. (2004). Grobnitsata v Aleksandrovo. – In: Izvestiya na Istoricheski muzey – Haskovo, No. 2/2003, 149 – 175.Marazov, I. (1978). Kam semantikata na stenopisite ot Kazanlashkata grobnitsa. – In: Izkustvo, No. 7, 21 – 25.Rabadjiev, K. (2002). Elinski misterii v Trakiya (Opit za arheologicheski prochit). Sofia.Stoyanov, T. (2008). Za izobrazitelnata programa na grobnitsata ot Aleksandrovo. –Arheologiya, No. 49/1 – 4, 57 – 67.Vasilchin, I. (2006). Vtori trakiyski nekropol kray selo Dobrina, Provadiysko. – Izvestiya na narodniya muzey – Varna, No. 40(55), 124 – 131.Alcock, J. P. (2006). Food in the Ancient World. Food Through History. London: Greenwood Press.Bacon, J. (1991). Kalach, Kolatch, Kulitch-Challah? – In: Oxford Symposium on Food & Cookery 1990. Feasting and Fasting. Proceedings (ed. Harlan Walker). London, 53 – 54.Baughan, E. P. (2013). CouchedinDeathKlinai and IdentityinAnatolia and Beyond. Wisconsin: The University of Wisconsin Press.Becker, W. A. (1889). Charicles or Illustrations of the Private Life оf The Ancient Greeks with Notes and Excursuses. London.Brosius, M. (1996). Women in Ancient Persia, 559 – 331 BC. New York: Oxford University Press.Delemen, İ. (2006). An Unplundered Chamber Tomb on Ganos Mountain in Southeastern Thrace. – American Journal of Archaeology, vol. 110, No. 2, 251 – 273.Fol, V. (2021). A Temple in the Sarafova Tumulus near the Town of Krun. In: Cinnabar – the Royal Colour in Thracian and Roman Cultures in the Bulgarian Lands (eds. Valeria Fol, Ruja Popova, Rossitsa Manova). Sofia, 98 – 103.Moullou, D., et al. (2012). Lighting in Antiquity. – In: 5th Balkan Light International Conference, Belgrade 5 – 6 October 2012 (ed. Svetlana M. Kostic). Belgrade, 237 – 244.Popova, R. (2021). Tholos Tomb below the Tyulbeto Tumulus Kazanlak. In: Cinnabar – the Royal Colour in Thracian and Roman Cultures in the Bulgarian Lands (eds. Valeria Fol, Ruja Popova, Rossitsa Manova). Sofia, 52 – 61.Popova, R. (2021). Tomb with Frescoes near the Village of Alexandrovo. In: Cinnabar – the Royal Colour in Thracian and Roman Cultures in the Bulgarian Lands (eds. Valeria Fol, Ruja Popova, Rossitsa Manova). Sofia, 82 – 97.Richter, G. M. A. (1966). The Furniture of the Greeks Etruscans and Romans. London: The Phaidon Press.Rouillard, P., & Verbanck-Piérard, A. (2003). Le vase grec et ses destins. Münich.Sechrist, R. (2017). Planet of the Grapes: A Geography of Wine. California: ABC-Clio.Suk Fong Jim, T. (2011). The vocabulary of ἀπάρχεσθαι, ἀπαρχή and related terms in Archaic and Classical Greece. – Kernos, No. 24, 39 – 58.Wecowski, M. (2014). The Rise of the Greek Aristocratic Banquet. Oxford.Online Sources:Fol, A. Risuvanite trompeti v Kazanlashkata grobnitsa: paraleli s trompetite na Tutankamon, instrumentalni i izpalnitelski hipotezi. – In: Ancient Thrace and Thracians Online Encyclopedia. https://www.thracians.net/religion-bg-bg/52-музика/630-рисуваните-тромпети-в-казанлъшката-гробница-паралели-с-тромпетите-на-тутанкамон,-инструментални-и-изпълнителски-хипотези (accessed 01.04.2023).Gicheva-Meimari, R. (2019). ‘Pogrebalnoto lozhe’ na trakiyskite aristokrati. –Nauchen elektronen arhiv na NBU (unpublished). https://eprints.nbu.bg/id/eprint/4122 (accessed 20.05.2023).Popov, D. Tsarskata obikolka. – In: Ancient Thrace and Thracians Online Encyclopedia. https://www.thracians.net/kings-bg-bg/27-царска-обредност/89-царска-обиколка (accessed 17.04.2023).Porozhanov, K. Odriski vladetelski rezidentsii-kreposti. – In: Ancient Thrace and Thracians Online Encyclopedia. https://www.thracians.net/state-organization-bg/38-селища-градове-резиденции/204-одриски-владетелски-резиденции-крепости (accessed 18.04.2023).Liddell, H. G., & Scott, R. (1940). A Greek–English Lexicon: Revised and Augmented Throughout by Sir Henry Stuart Jones with the assistance of Roderick McKenzie. Oxford: Clarendon Press. http://www.perseus.tufts.edu/hopper/text?doc=Perseus:text:1999.04.0057:entry=zwmo/s (accessed 20.04.2023).
Keywords: Thracians; feast; banquet; symposium; etiquette; table manners